The potential of cold plasma technology for weed control in the pre-growth and post-growth phases - ANWAR BUKHORI; DWI GUNTORO; SUDRADJAT SUDRADJAT; ANTO TRI SUGIARTO (Society for Indonesian Biodiversity, 2024)
Abstract. Bukhori A, Guntoro D, Sudradjat, Sugiarto AT. 2024. The potential of cold plasma technology for weed control in the pre-growth and post-growth phases. Biodiversitas 25: 3628-3636. Efforts to reduce the use of herbicides can be made by using cold plasma technology. This technology produces heat energy through the emission of UV plasma light, generated by electrical energy. This research investigates the potential of various cold plasma treatments to inhibit germination, inhibit the growth of weed seeds in soil media, and suppress weed growth. The study was conducted at the Ecotoxicology Laboratory and Seed Propagation Laboratory, Institut Pertanian Bogor, Bogor, Indonesia, from March to September 2023. Three types of weeds used were Asystasia gangetica (L.) T.Anderson, Cyperus rotundus L., and Eleusine indica (L.) Gaertn. Three experiments were designed for this study. The first experiment tested cold plasma on weed seeds, the analysis was conducted using a single-factor completely randomized designed with varying doses of cold plasma and four replications. The second experiment tested cold plasma technology in soil media, the analysis was conducted using a single-factor completely randomized designed with various doses of cold plasma and seven replications. The third experiment tested cold plasma on the growth of each weed, the analysis was conducted using a single-factor randomized block design with various doses of cold plasma and four replications. The research shows that the application of cold plasma at a dose of 14 kV for 85 seconds can inhibit germination and weed growth in soil media of each type of weed A. gangetica, C. rotundus, and E. indica.